Wishing for Seven Sons and One Daughter - Dzhabbarov, Ali-Isa (Azerbaijan, 2002)
The traditional Azerbaijani wedding wish serves as the title to this film and appears to be just a flowery ritual formula. Yet the colorful ethnographic scenes reveal a tragedy that has lasted since time immemorial. In this patriarchal society, girls are unwanted and "useless". In the past, new-born girls were often simply killed; yet, since the development of ultrasound, women have been compelled to seek abortions. Such an attitude towards women occasionally results in terrible family tragedies, one of which shook Azerbaijan a few years ago. This film is part of the Gender Montage: Paradigms in Post Soviet Space film series made by The Network Women's Program of the Open Society Institute - Russia and the Gender Policy Institute.
Keywords: Documentary films